Ultra-processed food addiction symptoms profile according to weight status among Brazilian adults - Silva Júnior, André Eduardo; Macena, Mateus de Lima; Paula, Déborah Tenório da Costa; Soares, Délis Barbosa; Gama, Isabelle Rodrigues de Souza; Lopes, Natália Gomes da Silva; da Silva, Maria Eduarda de Carvalho Macário; Gearhardt, Ashley Nicole; Bueno, Nassib Bezerra (Frontiers in Psychiatry, 2025)
IntroductionThe study aimed to investigate several ultra-processed food (UPF) addiction symptoms according to the weight status and to verify if there are specific symptoms of UPF addiction that differ according to the weight status in adults with a UPF addiction diagnosis.MethodsThis is a cross-sectional study that included adults (18–59 years) of both sexes with UPF addiction diagnosis. Demographic and clinical data were collected, such as body mass index (BMI), diagnosis of depression, and generalized anxiety disorder (GAD). UPF addiction was assessed using the modified Yale Food Addiction Scale 2.0.ResultsIn total, 1,074 participants were included. Of this total, 83.3% (n = 895) were female, with a mean age of 23 ± 5 years, of which 36.8% (n = 395) were classified with normal weight, 31.9% (n = 343) with overweight, 19.5% (n = 209) with obesity I, 8.1% (n = 87) with obesity II, and 3.7% (n = 40) with obesity III. The prevalence of UPF addiction symptoms referring to social/interpersonal harm, cut down/quit, role interference, and physical/psychological harm increased progressively with increasing BMI, even after adjusting for age, sex, diagnosis of depression, and GAD.ConclusionThis study showed a progressive increase in UPF addiction symptom severity with rising BMI levels. Moreover, distinct UPF addiction symptom profiles emerged across various BMI categories. Understanding these nuances can guide the development of targeted interventions and treatment strategies to address this multifaceted behavioral profile effectively. Further research across different populations is imperative to broaden our comprehension of UPF addiction’s impact and expression.